Pendampingan Ibu Hamil dalam Upaya Pencegahan Komplikasi Kehamilan Melalui Kelas Ibu Hamil di Wilayah Kerja Puskesmas Kinovaro Kabupaten Sigi - Enggar Enggar; Srigita Dewiyana; Alya Mahira; Kiran Violeta Mamahit; Ghita Melati Putri; Astri Febriana Iffaf (FKIP, Universitas Palangka Raya, 2026)
Pregnancy complications remain a leading cause of maternal morbidity and mortality in Indonesia. Pregnant women's limited knowledge of pregnancy danger signs and suboptimal participation in antenatal care (ANC) services can increase the risk of delayed detection and management of pregnancy complications. The Kinovaro Community Health Center (Puskesmas) in Sigi Regency is one of the areas requiring maternal health information and activities that can increase pregnant women's participation in health education activities. This community service activity aims to improve pregnant women's knowledge and preparedness in preventing pregnancy complications through mentoring based on Pregnant Women's Classes. The activity involved eight pregnant women in their second and third trimesters. The methods used included health education, interactive discussions, simple pregnancy check-ups, pregnancy exercise demonstrations, and evaluation using pre- and post-tests. The results showed that all participants actively participated in the activity and had a good level of knowledge after participating. The average knowledge score increased from 77.5 to 80.0, an increase of 3.2%. In addition, participants were able to identify pregnancy danger signs, understand the importance of standard ANC visits, and practice pregnancy exercise movements independently. This activity demonstrates that mentoring through the Pregnant Women's Class can strengthen maternal health literacy, increase pregnant women's preparedness in recognizing pregnancy complications, and support the strengthening of maternal health services at the community level.